2020
DOI: 10.21577/0103-5053.20190144
|View full text |Cite
|
Sign up to set email alerts
|

Dextrorotatory Chromomycins from the Marine Streptomyces sp. Associated to Palythoa caribaeorum

Abstract: A Streptomyces sp. (BRA-384) was selected among nine strains of bacteria isolated from the zoanthids Palythoa caribaeorum due to the high cytotoxic activity presented by its EtOAc extract (inhibitory concentration mean (IC 50) of 2 ng mL-1) against colon cancer cell line. From the EtOAc extract of BRA-384 three new chemical entities (A 6 , A 7 and A 8) and one dextrorotatory chromomycin (A 5), a promising class of anticancer compounds, were identified. The cytotoxicity of chromomycins A 5 to A 8 was tested aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The compounds are distinguished by the type of sugar; chromomycins have a disaccharide chain consisting of two d -olioses at C-2 and a trisaccharide chain consisting of two D-olivoses and L-chromose. Chromomycins possess a broad range of biological activities such as antimicrobial [ 10 , 11 ], anticancer [ 12 , 13 , 14 ], and antiviral [ 15 ] activities, and are found in terrestrial and marine bacteria of the genus Streptomyces . Similar to other aureolic acid family members, chromomycins interact with the DNA helix minor groove in regions with high GC content and in a non-intercalative way with Mg 2+ cations, causing DNA damage in treated cells [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The compounds are distinguished by the type of sugar; chromomycins have a disaccharide chain consisting of two d -olioses at C-2 and a trisaccharide chain consisting of two D-olivoses and L-chromose. Chromomycins possess a broad range of biological activities such as antimicrobial [ 10 , 11 ], anticancer [ 12 , 13 , 14 ], and antiviral [ 15 ] activities, and are found in terrestrial and marine bacteria of the genus Streptomyces . Similar to other aureolic acid family members, chromomycins interact with the DNA helix minor groove in regions with high GC content and in a non-intercalative way with Mg 2+ cations, causing DNA damage in treated cells [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, CA 2 had an IC 50 of 18.8 nM in the metastatic melanoma cell line Malme-3M and was thus less cytotoxic than the CA 5 and CA 6 chromomycins tested in this study against melanoma cells (Guimarães et al, 2014). Furthermore, a recent study from our group compared the cytotoxicity of 4 different chromomycins in a 5 human tumor cell line panel and showed that CA 5 was the most potent, especially against the MM200 (IC 50 of 0.2 nM) and 501Mel (IC 50 of 0.8 nM) melanoma cells (Pinto et al, 2019).…”
Section: Ca 5 Displays Potent Cytotoxicity Against Different Tbx2-drimentioning
confidence: 63%
“…Most of the available reports on this class of molecules regard the biological properties of CA 3 and, to a less extent, of CA 2 . These chromomycins are, in turn, stereoisomers of CA 6 and CA 5, respectively, as demonstrated by Pinto et al (2019) and Pettit et al (2015). CA 3 binds to the minor groove of the DNA complex as a dimer in a process dependent on Mg +2 , in which a portion of the chromophore along with the D, E and F sugar moieties interact with residues of the minor groove, while the A and B sugar moieties and another portion of the chromophore interact with the phosphate backbone (Gao and Patel, 1989;Boer et al, 2009).…”
Section: Cell Linementioning
confidence: 88%
See 2 more Smart Citations